Synthesis of nickel nanoparticles via non-aqueous polyol method: effect of reaction time - Nik Roselina, N.R; Azizan, A; Lockman, Z (Universiti Kebangsaan Malaysia, 2012)
This paper presents facile and rapid synthesis route of Ni nanoparticles at approximately 180°C in the mixture composed of ethylene glycol (EG) with hydrazine (N2H4) as a reducing agent. X-ray diffraction (XRD) analysis revealed that Ni2+ can be reduced completely to Ni metal in 15 min. XRD analysis also indicated that the as-synthesized nanoparticles were pure Ni with face-centered cubic (fcc) crystal structure. Transmission electron microscopy (TEM) results showed that the sample with heating duration of 15 min has the most narrow size distribution and the size increased as the reaction time increased.